Reversible Superwetting Transition Between Superhydrophilicity and Superhydrophobicity on a Copper Sheet, and Its Corrosion Performance - Li, Hong; Chen, Tiange; Lu, Yanfeng; Fu, Xinyu; Chu, Xingwen; Liu, Qinzhuang; Zhang, Jinfeng (Frontiers in Materials, 2021)
Dense copper oxide nanoribbons arrays are prepared on a copper sheet by using a low-temperature hydrothermal method. The wettability of the surface modified by stearic acid is superhydrophobic, and the water contact angle is 153.6°. It is demonstrated that the reversible transition from superhydrophilicity to superhydrophobicity is successfully achieved by heat treatment and re-modification, and the whole process can be accomplished in 170 s. Potentiodynamic polarization curves and Nyquist curves show that these superhydrophobic surfaces have good corrosion resistance and superior durability.